On the dynamics of cutting arc plasmas: the role of the power supply ripple - Prevosto, Leandro (2012)
The power sources used in cutting arc torches are usually poorly stabilized and have a large ripple factor. The strong oscillatory components in the voltage and arc current produce in turn, large fluctuations in the plasma quantities. Experimental observations on the dynamics of the nonequilibrium plasma inside the nozzle of a 30 A oxygen cutting torch with a 7 % ripple level of its power source are reported in this work. The observed electron temperature (mean value º 5400 K) shows a rms deviation º 5 % (≤ 300 K), which is of the order of the arc voltage ripple level. A considerable different situation occurs with the plasma density (mean value º 3 ´ 1019 m-3). In this case the rms deviation was º 75 %, much greater than that of the electron temperature.